Benchmark study on motions and loads of a 6750-TEU containership. (1st June 2016) - Kim, Yonghwan; Kim, Jung-Hyun
Abstract: This study deals with a benchmark test on the performance of seakeeping analysis codes, which was carried out as part of the 2nd ITTC–ISSC joint workshop in 2014. Eleven institutes participated in the benchmark test with seventeen analysis codes. The target ship was the 6750-TEU containership, and the test of its flexible scale model was conducted by KRISO. A test matrix was composed of one condition for linear responses and three conditions for nonlinear responses. Participants were requested to conduct computational simulations and submit their heave, pitch, and vertical bending moment results in head regular waves. The computational results obtained are compared with each other using statistical analysis. The comparison reveals the performances and trends of the computational results. In addition, all the model data is included in the paper in order to encourage readers to participate in the benchmark test. Highlights: Benchmark test results are introduced for ship structural loads in waves. Eleven set of computational results are compared for the benchmark test. Most results showed that they are within a bandwidth, showing same trend. There are some difference in hydroelastic case.